2022
DOI: 10.37467/revhuman.v11.4048
|View full text |Cite
|
Sign up to set email alerts
|

Responsabilidad social universitaria, gestión y políticas educativas

Abstract: La universidad es objeto de escrutinio y análisis permanente, tanto por su importancia histórica su acervo académico y de producción discursiva. Así, el concepto de responsabilidad social universitaria (RSU), de origen empresarial, genera un marco de orientación y organización universitarias. El objetivo de este artículo es develar los discursos desde los que el concepto de RSU permea la gestión y las políticas educativas universitarias en Colombia. Mediante el análisis crítico discursivo (ACD) realizado se en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…It is important to analyze the aspects related to social impacts and implications for universities in the region. [10]. Thus, one of the main aspects to be taken into account is the role of universities in Latin America and how USR has developed over time in this context [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to analyze the aspects related to social impacts and implications for universities in the region. [10]. Thus, one of the main aspects to be taken into account is the role of universities in Latin America and how USR has developed over time in this context [20].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the production in USR is a topic that provides future lines for literature framed in strategic impact management policies, users and their stakeholders, servicelearning and strategies of University Social Responsibility [5]. Likewise, it was found that the articles with the highest number of citations were: University social responsibility as a challenge for the strategic management of Higher Education and University social responsibility: a student base analysis in Brazil with 60 and 42 citations respectively; which implies that the research seeks to determine aspects that promote cultural change and incorporate institutional policies that promote interest in USR [34,10].…”
Section: Discussionmentioning
confidence: 99%
“…La presente investigación es de corte cualitativo y se realiza atendiendo a que las comunidades son en sí mismas espacios de representación y que existen entre ellas dinámicas de interlocución que develan la posibilidad de una construcción colectiva de saberes que emanan del entramado de la cotidianidad (Cabanzo, 2012). Así, la primera parte del ejercicio requirió de una revisión bibliográ ca sobre estudios de familia, relaciones padres e hijos, comunicación y otros contenidos como aproximaciones al tema para hacer un balance documental sobre posturas que justi can la articulación de la familia con los entornos y población universitaria en aras de fortalecer su calidad de vida.…”
Section: Metodologíaunclassified